Discursive limitations and opportunities in environmental media communication - Gunnars, Therese (2021)
In 2017, Preem started the process for applying for an expansion of their oil refinery, Preemraff Lysekil. The announcement of their plans sparked debate in the media, where environmental organizations opposed the project and appealed the application for expansion. Simultaneously, Preem produced a written advertisement campaign that was published in various Swedish newspapers. The campaign focused on positive effects of an expansion of Preemraff Lysekil, as well as other commitments to sustainability taken on by Preem, and was criticized by environmental organizations for greenwashing. Preem ultimately withdrew their application before it had been approved, but stated that it was not for environmental reasons but rather economical. Despite their lack of environmental concerns in their decision to withdraw their application, Preem has since been voted Sweden’s greenest fuel brand, indicating that their brand is associated with sustainability. I have researched the use of discourses between three different actors involved in the debate about Preemraff Lysekil; Preem, Greenpeace and Swedish Society for Nature Conservation (SSNC). The focus of this study has been to gain a deeper understanding of how the different actors used language during the debate and how change knowledge was expressed by the mentioned actpors. The thesis shows that Preem has possessed more discursive opportunities in their communication compared to Greenpeace and SSNC, and that Greenpeace and SSNC may have been restricted by overarching social practices in their responses to Preem.